Functional and Radiological Outcome of Longer Lever Arm Plates with Minimally Invasive Plate Osteosynthesis (MIPO) in AO Type C Distal Femoral Fracture (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To evaluate the treatment outcome in AO type C, distal femoral fractures using longer lever arm anatomical plates with minimally invasive plate osteosynthesis (MIPO) technique.Methods: This prospective cases series was done using probability sampling technique at two centers including Orthopedics and Spine Institute, Doctors Hospital, Medical Center, Lahore and Department of Orthopedics Surgery and Traumatology, Post-graduate Medical Institute, Lahore General Hospital, Lahore from January 2016 to August 2017. AO type C close distal femoral fractures fulfilling the inclusion criteria were included in the study. We fixed all fractures with longer lever arm anatomical plates with minimally invasive plate osteosynthesis (MIPO) technique. On each follow up patients were assessed using American Knee Society Score(AKSS) for functional outcome and x rays for union. SPSS version 20.00 was used to analyze the data and p-value